Enzyme Inhibitor from Marine Organisms - Tischler, Dirk (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Marine habitats are promising sources to identify novel organisms and compounds. A total of 70% of the planet's surface is covered by ocean, and little is known about the biosphere within these habitats. In the last few years, numerous novel bioactive compounds or secondary metabolites from marine environments have been described. This is, and will be, a promising source of candidate compounds in pharma research and chemical biology. In recent years, a number of novel techniques have been introduced to the field and it has become easier to actually (bio-)prospect compounds such as enzyme inhibitors. Those novel compounds then need to be characterized and evaluated in comparison to well-known representatives. This Special Issue focuses on the description of novel enzyme inhibitors of marine origin, including bioprospecting, omic approaches, and structural and mechanistic aspects.